IMPROVEMENT ASSESSMENT OF MASTOLOGIST IN THE BREAST ONCOPLASTIC AND RECONSTRUCTIVE SURGERY OF SANTA CASA DE BELO HORIZONTE, MG, BRAZIL - Pires, Douglas de Miranda; Baroncelli, Carolina Lemos; Urban, Cicero de Andrade; Valadares, Carolina Nazareth; Andrade, Izabel Aparecida Cunha; Nascimento, Mariana dos Santos (Mastology, 2017)
Objective: This study aims to investigate the efficacy and improvement of knowledge acquired by breast cancer specialists in a postgraduate course of Oncoplastic Surgery conducted in Santa Casa de Belo Horizonte (SCBH). Method: For this evaluation, an exploratory qualitative study was carried out. It was supported by an online survey questionnaire sent to 36 breast cancer specialists, who had taken the course in the period from 2012 to 2014. The data were interpreted using statistical methods, as well as probabilistic sampling. Results: After the Oncoplastic Surgery course, almost all breast cancer specialists who had taken it demonstrated the ability to reconstruct the breasts of women who had undergone mastectomies with oncoplastic techniques. A large portion of the specialists was able to develop bilateral treatment with breast reduction, mastopexy and rebuild areolas and nipples, as well as immediately reconstruct the breast with expanders or prosthesis and contralateral symmetrization. A significant amount of professionals was able to perform breast reconstruction with autologous flaps. Conclusion: The course for the Professional Development of Breast Cancer Specialists sponsored by the Teaching and Research Institute of Santa Casa de Belo Horizonte was able to improve the skills of the professionals involved in the different breast remodeling and reconstruction techniques. This enables a paradigm shift in the treatment of cancer patients.